Representation of Victim and Perpetrator in Adelina Lisao’s Abuse Case in Malaysian Online News Articles - binti Adanan, Aizatul Alyaa; binti Ungku Mohd Nordin, Ungku Khairunnisa (Future Science, 2024)
This research analyses the representation of victim and perpetrator as social actors and its argumentation strategies from Malaysian online news articles surrounding the tragic case of Adelina Lisao, an Indonesian domestic worker who lost her life in Malaysia due to abuse by her employer. Employing a qualitative research approach, the data is systematically collected with keywords to identify relevant news articles pertinent to the case: